Zarządzanie środkami pieniężnymi w mikroprzedsiębiorstwach - Prędkiewicz, Katarzyna (Cash Management in Microcompanies, 2008)
Research results indicate that microfirms have higher relations of cash to current liabilities and assets than bigger companies. In this paper, the author tries to identify reasons of phenomena mentioned above and analyze available short and long-term instruments of money market for microcom-panies. The main reasons of high level of cash in microcompanies are: limited possibility of investing temporary cash surplus, conservative working capital strategy, specificity of investing cycle, and limited access to outside capital.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 473-481